2019
DOI: 10.24843/jbiounud.2019.v23.i01.p05
|View full text |Cite
|
Sign up to set email alerts
|

Number of spermatogenic cells and testes histology of mice (Mus musculus L.) after treated with different times and intervals of red calliandra (Calliandra calothyrsus Meissn.) leaf extract

Abstract: Tannin compounds in the form of tanic acid are known to inhibit the acrosine activity of spermatozoa and plasminogen activator, which is an antifertility mechanism. Red Calliandra (Calliandra calothyrsus Meissn.) leaves have the potential to be developed as herbal medicines, but these leaves contain high condensed tannins, so research needs to be done to determine the effect of red kaliandra leaf extract on the reproduction of male mice.This research used a completely randomized design (CRD) in a factorial pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
(3 reference statements)
0
0
0
1
Order By: Relevance
“…In this case, the Flavonoid compounds in the extract stimulate estrogen synthesis in mammals because their chemical structure is similar to that of estrogen. So that it can cause a decrease in FSH and LH production, and a decrease in LH synthesis will trigger a decrease in hormone synthesis by the Leydig cells in the testes [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the Flavonoid compounds in the extract stimulate estrogen synthesis in mammals because their chemical structure is similar to that of estrogen. So that it can cause a decrease in FSH and LH production, and a decrease in LH synthesis will trigger a decrease in hormone synthesis by the Leydig cells in the testes [5].…”
Section: Discussionmentioning
confidence: 99%
“…Harris and Septiana [4], in their research on the effect of giving brotowali plant extract on the reproductive system of male mice, stated that giving brotowali extract had an apparent effect in the form of a decrease in the number of spermatogenic cells in each section of the seminiferous tubules of mice. Pranadya et al, [5], in their research on the number of spermatogenic cells and testicular histology after administration of red calliandra leaf extract, stated that the given calliandra leaf extract caused a decrease in the number of spermatogenic cells in the seminiferous tubules of white rats (Rattus norvegicus L.) Yasmin et al, in their research on the effect of giving bitter gourd ethanol extract to seminiferous tubule tissue in male mice, stated that giving bitter gourd ethanol extract could reduce the thickness of the seminiferous tubules with the optimal dose of 1,120 mg/kgBB day. While Anzila et al, [6] concluded that the administration of basil extract on mouse males (Rattus norvegicus L.) Balb-c strain with 200 mg/kg BW has the potential to enhance the process of spermatogenesis or as a fertility agent.…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis sel spermatogenik berhubungan dengan dampak sitotoksik. Sedangkan efek sitostatik melibatkan penghambatan sel spermatogenik yang secara aktif berkembang biak serta pengurangan metabolisme sel spermatogenik dengan mengganggu keseimbangan sistem hormonal (Pranadya et al, 2019).…”
Section: Sel Spermatidunclassified